Making Ideals a Reality: Curtin's African Virtual University Experience - Siragusa, Lou; Wright, Fiona; Boase-jelinek, Daniel; Kulski, Martijntje (IDP Australia, 2004)
Curtin University of Technology in partnership with the African Virtual University (AVU) is delivering accredited diploma and degree programmes in Business to four AVU partner institutions in Ethiopia, Kenya, Rwanda and Tanzania. Both programs are designed to prepare students for a professional career and to produce flexible, creative and entrepreneurial graduates who can contribute to the development of new business enterprises in Africa. Delivery of these programs is in English and in a flexible format. Multiple modes of delivery are used including online course materials, synchronous and asynchronous discussion forums, CD-ROMs, real time and pre-recorded lectures, videos, textbooks and supplementary notes. The challenges of providing multi-mode learning materials to Africa and elsewhere include the need to adapt these materials to suit the technical, financial and human resources of participating institutions as well as the cultural preferences, English language ability and learning styles of participating students. Curtin has implemented a range of strategies to address these challenges, towards a Project goal of establishing a model of best practice for the design and delivery of mixed mode transnational education. This paper describes the strategies adopted by Curtin in the design, delivery and evaluation of the educational materials and associated staff and student support, as well as the outcomes and lessons learnt from the first semester.